Analisis Perbandingan Struktural Cerbung "Kuburan Tanpa Tenger" Karya Margareth Widhy Pratiwi dengan Film Thailand "Alone" - Dwi Anjani Wulan Ndari; Herlina Setyowati; Eko Santoso; Aris Aryanto (Sutasoma : Jurnal Sastra Jawa, 2022)
The purpose of this study is to describe the instrinsic elements of the serial story Kubur Tanpa Tenger and the Thailand film Alone, describe the comparison of themes in the serial story Kubur Tanpa Tenger with the Thailand film Alone, describe the comparison of the characterizations in the serial story Kubur Tanpa Tenger with the Thailand film Alone, and describe the comparison of the setting in the serial story Kubur Tanpa Tenger with the Thailand film Alone. The research method is descriptive qualitative. The data sources of this research are the serial story Kubur Tanpa Tenger by Margareth Widhy Pratiwi and the Thailand film Alone 2007. The data collection technique was obtained by the listening method followed by the note-taking technique. The data analysis technique used the diachronic comparison method. The results of the research are stories from the serial story Kubur Tanpa Tenger and the Thailand film Alone, which tells the life story of one twin sister who was terrorized by the spirit of the other twin after he died. The similarity of the contents of the two stories is what makes the intrinsic elements in the form of themes, characterizations and settings have similarities and differences, this is because these two stories come from different countries. Keywords: Comparative Literature; Serial; Films